Benjamin Lax : Interviews on a Life in Physics at MIT. - Stevenson, Donald T.; Reine, Marion B.; Aggarwal, R. L. (Roshan Lal), 1937- (Milton, UNITED KINGDOM : CRC Press LLC, 2019)
This book covers the life and 60-year career of Prof. Benjamin Lax (1915-2015), a preeminent physicist at the Massachusetts Institute of Technology (MIT), who played major roles in the development and applications of solid state and plasma physics. In an extensive series of autobiographical interviews, Lax describes the challenges he overcame, the opportunities he embraced, and the many outstanding research physicists he recruited, mentored, and interacted with. He includes both personal and professional reminiscences. Lax begins with his earliest memories of his childhood in Hungary. He recalls the immigration of his family to America and his education in New York City. He describes his Army service as a Radar Officer at the MIT Radiation Laboratory during World War II. He covers his graduate education in physics at MIT, andhis building up the semiconductor and ferrite research groups at MIT Lincoln Laboratory in the 1950s. He describes the origins and accomplishments of the MIT Francis Bitter National Magnet Laboratory, of which he was the founding Director, and recalls his tenure as professor in the MIT physics department. Features: Provides a valuable insight into a 60-year career in physics at one of the world's major research universities, the Massachusetts Institute of Technology Explores the organization, funding, and conduct of solid state physics research in the second half of the twentieth century Includes a complete bibliography of Lax's publications in an online supplement
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Physics; SCIENCE / General; SCIENCE / Research & Methodology; Lax, Benjamin -- Interviews; Physicists -- United States -- Interviews; Physicists -- United States -- Biography